MANUSCRIPT DECORATIONS: ILLUMINATIONS AND ILLUSTRATIONS ON SOME EXISTING MANUSCRIPTS IN KERINCI - Nurfalina, Yuliana; Hidayat, Ahmad Taufiq; Riza, Yulfira (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2023)
ABSTRACTThis research is presented to examine the decoration contained in the manuscripts in Kerinci, because it is seen from the problem that in the development of civilization and the tradition of writing manuscripts it is common to change the form of illumination and illustration in manuscripts due to various factors which are the result of human creativity. For the method that the author uses in this research is using a qualitative method with a codicological approach, whose primary source focuses on several Kerinci manuscripts that have been digitized. Then for other sources this research is assisted by references such as books, articles, and other sources related to this study. The result of this paper is knowledge and description of the decoration on the manuscript in the form of illumination and illustration on several manuscripts found in the Kerinci region in the form of manuscript decoration and explanation of the meaning of the contents of the manuscript.Keywords: Decoration, Script, Illumination, Illustration, Kerinci.Â ABSTRAKPenelitian ini dihadirkan untuk menelisik hiasan yang terdapat pada naskah yang ada di Kerinci, dikarenakan dilihat dari persoalan bahwa dalam perkembangan peradaban dan tradisi penulisan naskah lumrah terjadi perubahan bentuk iluminasi maupun ilustrasi pada naskah karena disebabkan oleh berbagai faktor yang merupakan hasil dari kreativitas manusia. Untuk metode yang penulis gunakan dalam penelitian ini yaitu memakai metode kualitatif dengan pendekatan kodikologi, yang sumber primernya berfokus kepada beberapa naskah-naskah Kerinci yang sudah digitalisasi. Kemudian untuk sumber-sumber lainnya penelitian ini dibantu oleh referensi seperti buku, artikel, dan sumber lainnya yang berkaitan dengan kajian ini. Adapun hasil dari tulisan ini adalah pengetahuan dan deskripsi tentang hiasan pada naskah berupa iluminasi dan ilustrasi pada beberapa naskah yang terdapat di wilayah Kerinci yang berupa hiasan naskah dan penjelasan dari makna isi naskah.Kata Kunci:Â Hiasan, Naskah, Iluminasi, Ilustrasi, Kerinci.